2018
DOI: 10.1186/s12974-018-1316-0
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of gene expression profiles in the rat dorsal horn of the spinal cord using RNA sequencing in chronic constriction injury rats

Abstract: BackgroundNeuropathic pain is caused by damage to the nervous system, resulting in aberrant pain, which is associated with gene expression changes in the sensory pathway. However, the molecular mechanisms are not fully understood.MethodsWistar rats were employed for the establishment of the chronic constriction injury (CCI) models. Using the Illumina HiSeq 4000 platform, we examined differentially expressed genes (DEGs) in the rat dorsal horn by RNA sequencing (RNA-seq) between CCI and control groups. Then, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
7
17
0
Order By: Relevance
“…And previous study showed that the expression of GAT-1 increased in CCI models, and administration with GAT-1 inhibitor can relieve mechanical hypersensitivity (Daemen et al 2008). Hui Du et al using RNA sequencing indicated that CXCL13 is increased in spinal cord in CCI rats (Du et al 2018). It is consistent with our experimental results.…”
Section: Discussionsupporting
confidence: 91%
“…And previous study showed that the expression of GAT-1 increased in CCI models, and administration with GAT-1 inhibitor can relieve mechanical hypersensitivity (Daemen et al 2008). Hui Du et al using RNA sequencing indicated that CXCL13 is increased in spinal cord in CCI rats (Du et al 2018). It is consistent with our experimental results.…”
Section: Discussionsupporting
confidence: 91%
“…According to the sequencing data from the injured DRGs ( Wu et al, 2016 ), we observed similar expression changes of some genes such as the upregulation of Atf3, Ccr1, Ccr5, and Gal, and the downregulation of Gria2 in the spinal cord as well as the elevated expression of Cacna2d1 and the reduced expression of Gabra1 in the ACC and AMY after SNL. Besides, we found the consistent expression patterns of some genes such as the upregulation of Atf3, Bdnf, C1qa, C3, Cck, Ccl2, Cd68, Csf1, Cx3cr1, Gch1, Itgam, Ngfr, Pdyn, and Tlr2 in the spinal cord of SNL mice, when compared to the sequencing results in CCI rats ( Du et al, 2018 ; Korczeniewska et al, 2020 ). These data suggest the common gene expression patterns independent of regions, models, or species.…”
Section: Discussionsupporting
confidence: 58%
“…The SNI datasets (GSE18803) were downloaded from Gene Expression Omnibus (GEO) dataset, at the website of https://www.ncbi.nlm.nih.gov/geo/. The CCI datasets comes from a recently published article on CCI sequencing [29]. Differentially expressed genes from these microarray datasets were screened based on criteria as q value ≤ 0.01 and absolute value of |log 2 (Fold Change)| ≥ 1.0.…”
Section: Source Of Microarray Datamentioning
confidence: 99%